Answer:73
Step-by-step explanation:
Answer:
y = -6; -3; 0
Step-by-step explanation:
To quickly solve this problem, we can use a graphing tool or a calculator to plot the equation.
Please see the attached image below, to find more information about the graph
The equation is:
f(x) = 2x+2 , x < -3
f(x) = x, x = -3
f(x) = - x -2 , x > -3
From the graph, we can see that the values are
y = -6; -3; 0
The calculated average of a data set best describes A: Mean.
You could get two different functions out of this:
<u>2x + 2y = 8</u>
1). <u> 'y' as a function of 'x'</u>
Subtract 2x from each side: 2y = -2x + 8
Divide each side by 2 : <em> y = -x + 4</em>
2). <u> 'x' as a function of 'y' :</u>
Subtract 2y from each side: 2x = -2y + 8
Divide each side by 2 : <em> x = -y + 4</em>
Those two functions look the same, but that's just because the original
equation given in the problem was so symmetrical. In general, they're
not the same function.
Answer:
12.5x =10x+10
12.50x=x10+10
subtract 10x from both sides
2.5x=10
divide by 2.5
x=4